MARKET PERFORMANCE OF RED CHILI THROUGH SPOT AUCTION SYSTEM IN YOGYAKARTA PROVINCE - Ebban Bagus Kuntadi; Jamhari Jamhari (UPT Penerbitan Universitas Jember, 2012)
Red chili is one of horticulture commodity which has high economic value. The main problem of red chili marketing is the long of distribution channel that caused different of selling price between farmer and trader. In order to minimize that problem, its need spot auction system at farmer level. This distribution system is important to give best alternative in order increase red chili farmer income. Through this analysis, red chili’s farmer gets opportunity to decrease long channel distribution and increase selling price. This research results show that marketing margin at spot auction market is more efficient, through monopoly index analysis show that how big dominances of marketing institute in red chili marketing chain influence bargaining position of red chili farmer.